Impact of binding to the multidrug resistance regulator protein LmrR on the photo-physics and -chemistry of photosensitizers. Issue 21 (20th May 2020) - Mejías, Sara H.; Roelfes, Gerard; Browne, Wesley R.
Abstract : Binding of photosensitizing compounds to the LmrR protein with and without tryptophan residues has a profound and varied effect on their photochemistry and ability to generate reactive oxygen species. Abstract : Light activated photosensitizers generate reactive oxygen species (ROS) that interfere with cellular components and can induce cell death, e.g., in photodynamic therapy (PDT). The effect of cellular components and especially proteins on the photochemistry and photophysics of the sensitizers is a key aspect in drug design and the correlating cellular response with the generation of specific ROS species. Here, we show the complex range of effects of binding of photosensitizer to a multidrug resistance protein, produced by bacteria, on the formers reactivity. We show that recruitment of drug like molecules by LmrR (Lactococcal multidrug resistance Regulator) modifies their photophysical properties and their capacity to induce oxidative stress especially in 1 O2 generation, including rose bengal (RB), protoporphyrin IX (PpIX), bodipy, eosin Y (EY), riboflavin (RBF), and rhodamine 6G (Rh6G). The range of neutral and charged dyes with different exited redox potentials, are broadly representative of the dyes used in PDT.